ANALISIS DISTRIBUSI SELISIH TINGKAT PENGGANGGURAN TERBUKA (TPT) DAN TINGAT PARTISIPASI ANGKATAN KERJA (TPAK) MENGGUNAKAN GOOGLE COLAB - Muhammad Farid Dzakwan Wahyudi; Ananda Rafael Chrisvo; Muhammad Fatwa Hidayatullah; Jadiaman Parhusip (LPPM Politeknik Pratama Kendal, 2024)
This study examines the distribution differences between the Open Unemployment Rate (OUR) and Labor Force Participation Rate (LFPR) in Indonesia. Statistical data from 2023, sourced from the Central Bureau of Statistics, are analyzed using the Google Colaboratory platform. This cloud-based tool enables efficient data computation and visualization. The research utilizes a quantitative approach to calculate and explore provincial disparities in OUR and LFPR over two key periods, February and August 2023. Findings reveal distinct trends: some provinces experienced a rise in unemployment, while others observed significant labor market participation growth. The results contribute to labor policy planning and provide a model for similar analyses. However, limitations such as incomplete data and unaccounted external factors should be noted.